Tracing the evolutionary trajectory of the IncP-2 plasmid co-harboring blaIMP-45 and blaVIM-1: an outbreak of Pseudomonas aeruginosa co-producing IMP-45 and VIM-1 carbapenemases in China - Ma, Yiqun; Lei, Zichen; Zhang, Yulin; Liu, Qi; Zhang, Feilong; Zu, Hao; Yang, Xinrui; Li, Ziyao; Lu, Binghuai (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCarbapenem-resistant Pseudomonas aeruginosa (CRPA) poses a significant global health risk, particularly for immunocompromised individuals. This study documents an outbreak of CRPA strains co-harboring blaVIM-1 and blaIMP-45 on IncP-2 plasmids in a Chinese tertiary hospital, resulting in poor outcomes for transplant patients.Methods17 ST313 VIM-1-IMP-45 CRPA strains were collected from transplant patients, and antibiotic susceptibility was tested via microbroth dilution. Whole genome sequencing (WGS) identified drug resistance and virulence mechanisms, analyzed ST313 P. aeruginosa phylogeny, and traced blaVIM-1 and blaIMP-45 origins. Conjugation experiments were conducted to assess the conjugative potential of the IncP-2 plasmid co-harboring blaVIM-1 and blaIMP-45. Structural and molecular docking studies explored the PBP3 (P527S) mutation’s role in aztreonam resistance.ResultsFrom February 2022 to July 2024, 17 ST313 VIM-1-IMP-45 CRPA strains from 10 transplant patients were identified. All strains were extensively drug-resistant but sensitive to colistin and cefiderocol. WGS showed blaIMP-45 and blaVIM-1 on an IncP-2 megaplasmid. Phylogenetic analysis indicated high homology with plasmids carrying blaIMP-45. Further analysis of the genetic environment showed that the IncP-2 plasmid co-harboring blaVIM-1 and blaIMP-45 was formed by the insertion of a Tn3-family transposon carrying blaVIM-1 into the IncP-2 plasmid carrying blaIMP-45. In addition aztreonam-resistant strains (14/15) had a PBP3 (P527S) mutation, with molecular docking studies suggesting reduced aztreonam binding.ConclusionsThis study reports a clonal outbreak of ST313 P. aeruginosa strains co-producing IMP-45 and VIM-1 carbapenemases in a tertiary hospital. The evolutionary path of the IncP-2 plasmid co-harboring blaIMP-45 and blaVIM-1 was elucidated.